O complexo processo do Projeto de uma casa em Alcácer - Ana Catarina Moutinho Braga Loureiro (2017)
The following work arises from a request for an architectural project for a holiday home in Alcácer do Sal, which is the object of study for the present dissertation. This work portrays the experience and the strategies that were used to carry out a proposal to be presented to the client, mentioning the design's process, from the definition of an idea, to the relationship with the client, and, in the end, the final proposal. The project was developed bearing in mind the reference to the place, a relation between the architecture, the landscape and the social and cultural context in which it is inserted. Marcel Breuer's binuclear principle was equally important for the definition of a spatial organization and an architectural model that was proposed to the client, for it consisted in a multitude of references that were crucial for the definition of a strategy and concept design for the proposal in question. During the developmental process, the client imposed the elaboration of another project, from which two distinct proposals resulted: the client's proposal and a personal proposal, presented as an alternative. These two proposals were scrutinized in an attempt to understand what is the true experience of an architectural project, in which the impositions of a real client, with his own wishes and ideas, are very important in determining the final proposal. Therefore, it is expected that this study focuses primarily on this complex and dialectical process, where more than the final proposal a reflection on the whole process, inherent to its creation, is elaborated.